Associations of Education Level and Bone Density Tests among Cognitively Intact Elderly White Women in Managed Medicare. (26th September 2012) - Shi, Di; Yin, Michael T.; Shi, Qiuhu; Hoover, Donald R.
Abstract : Objectives . To examine associations between having bone density tests and level of education among white elderly women in managed Medicare. Method . Data from the ninth through twelfth cohort (2006–2009) of the Medicare Health Outcome Survey (HOS) of managed Medicare plans were analyzed; 239331 white elderly women were included. Respondents were grouped by education level and the percentages of respondents who had lifetime bone density testing done among each group were analyzed. Results . 62.7% of respondents with less than a high school education reported previously taking a bone density test. This was lower than the 73.8% for respondents who completed high school and the 81.0% for respondents with more than a high school education. When potential confounding factors such as age, body mass index, marital status, smoking history, year of HOS survey, and region were factored in, the odds ratios of having a bone density test when compared to respondents with less than a high school education were 1.61 and 2.39, respectively, for those with just a high school education and more than a high school education (P < 0.001 ). Conclusion . Higher education was independently associated with greater use of bone density test in these elderly white women.